TADZAWWUQ AL-LAHAJÂT AL-'ARABIYYAH 'ABR AL-TA'LÎM AL-ILIKTRÛNÎ : TADRÎS KITÂB AL-'ARABIYYAH AL-MU'ÂSHIRAH NAMÛDZAJAN - Masyhud, Fathin (Arabi : Journal of Arabic Studies, 2017)
The book al-Arabiyah al-Muashirah by German Leipziq University is a new phenomenon in Arabic teaching for non-Arabs using modern and easy methods coupled with animated voice and video recording through e-learning programs in the digital age. Direct dialectic instruction starts from the fourth theme which includes the Syrian, Iraq, Morocco and  Egyptian dialect. With this method, the students can compare the four dialects to understand and distinguish between them. State Islamic University Sunan Ampel is among the Islamic universities that implements the program in its Language Development Center. Learning dialectics with the book al-Arabiyah al-Muashirah was proved effective in giving the students a sense of pronunciation that differs from one resident to another.